Helicobacter pylori: Eradication or Preservation - Sachs, George (Faculty of 1000 Ltd, 2012)
Helicobacter pylori infects about 50% of the world’s population and inevitably results in the development of gastritis. Of those infected, about 10% develop peptic ulcer disease and roughly 1% develop gastric cancer. Conversely, some take the view that H. pylori infection provides some protection against gastro-esophageal reflux disease and possibly asthma. This review aims to explore the case for and against eradication of the bacterium using a “test and treat” approach amongst the general population.